Assessing the Participation of Indigenous Santals People in Chapainawabganj District of Bangladesh in Income Generating Activities - Ghosh, Mithun Kumar; Shoily, Afroza Awal; Islam, Md Shafiqul; Misu, Umma Musarrat; Khatun, Mst Afroza (The Agriculturists, 2020)
The study was conducted to determine the participation of indigenous people in different income generating activities (IGAs) and identify their problems. The study focused especially the Santal (an indigenous community of Bangladesh) peoples living in Chapainawabganj district. A pre-structured questionnaire was used to collect data through face to face interview from randomly selected sample size of 120 respondents. The Santals did not have recognizable access to education and income generating activities (IGAs). The main findings indicate that, most of the respondents were in between 29-50 years of age. About 60% of the respondents were illiterate with 80% belonged to medium sized family which consist of 4 to 6 members. Agriculture is the main occupation among of the respondents. Among them, only 3.33% people are involved with Government services. Most of the people are found without own land although they continue their livelihood mostly by crop production, livestock rearing, fish culture and day laboring. They take lease of cultivable land from others. The respondents had an average annual family income of about 71429BDT whereas about 80% of the respondents were under low income category. Lack of money was found the most important problem in the study area according to Focus Group Discussion (FGD). IGAs improved the overall livelihood status of the Santals in the study area. The Agriculturists 2020; 18(1) 137-143